Formulasi Lotion dari Ekstrak Buah Bit (Beta vulgaris) dengan Perbedaan Komposisi Asam Stearat - Fendi Yoga Wardana; Riska , Riska Milani (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2023)
Abstract. Lotion is a skin moisturizing cosmetic preparation that has non-greasy properties and is easily applied to the skin. This study aims to make a lotion formulation from beetroot (Beta vulgaris) extract according to the physical stability properties. In this study, three lotion preparation formulas were made with differences in stearic acid with a composition of 5%, 10% and 15%. Determination of the physical stability of the product is determined according to organoleptic, homogeneity, spreadability, pH and preference tests. The results showed that beetroot extract produced a yield percentage of 8.34%. Phytochemical screening showed that beetroot extract contains flavonoids, tannins, saponins and steroids or triterpenoids. Beetroot extract lotion was evaluated for 16 days. The results of the organoleptic evaluation on lotions F1, F2 and F3 showed no change. In the lotion homogeneity test F1, F2 and F3 produced a homogeneous lotion. Spreadability tests on F1, F2 and F3 had a spreading diameter of 4.5 – 5.5 g.cm/s. The pH test of lotions F1, F2 and F3 produced the same as a pH value of 7. F1 was the most preferred formula because all parameters give good results. Based on this study, it can be concluded that differences in stearic acid concentrations have no effect on the physical quality test of beetroot extract lotion preparations. Kata Kunci Buah bit, Lotion, Uji mutu fisik